Theoretical and methodological approaches to the study of generations: a comparative analysis - V. S. Novikova (Вестник Майкопского государственного технологического университета)
Abstract. The article defines the concept of «generation», and analyzes the transformation of this concept at various stages of the development of generational theory. The demographic approach to the study of generations is primarily associated with the identification of certain age intervals in order to analyze the age structure of the population. The author aims to supplement the demographic view of generations with a sociological interpretation of their features and characteristics. As a result of a theoretical review of generational concepts, the definition of the concept of «generation» has been formulated. A generation is understood as a group of people similar in value attitudes, behavior patterns and worldview, which were developed in the course of joint experience of historical events and socio-economic conditions with a common age interval of about 20 years.In the framework of the presented work, It has been assumed that generational theories and classifications have points of contact that allow them to be systematized and compared. To test this hypothesis, the generational classifications of Howe and Strauss, Yu.A. Levada, V.V. Radaev, and a number of other authors have been considered. The result of the theoretical review is a comparative analysis of these classifications in tabular form. As a result of the work, a number of recommendations for choosing a theoretical framework for studying generations depending on country and subject specifics have been provided. This study will be useful primarily for scientists studying generational issues in various fields of social sciences. Also, the presented article is relevant for educational programs that include consideration of generations as a scientific category.